Virtual reconstruction of the 1886 Edinburgh Veterinary College - Macdonald, Alastair A; Lad, Ketan; Hunzinger, Valentin J.; Warwick, Colin M. (Veterinary History Society, 2024)
n/a
Keywords: Veterinary History